COMMUNITY SERVICE DEMONSTRATION OF HYPERTENSION EXERCISES AND FOOT MASSAGE THERAPY AT POSYANDU ELDERLY TAMELANG DUSUN MEKARJAYA VILLAGE PURWASARI DISTRICT KARAWANG DISTRICT - Sarini, Sarini; Desty Lismayanti; Yanti Rosmayanti; Sumitro, Sumitro; Okti Rahayu Asih; Jumaedi, Jumaedi; Nining Sugihartati; Cindy Desrianti; Mutiara Puspita Asih (International Journal of Social Science, 2024)
Community service activities are carried out to educate the community about complementary therapies that can be done as an alternative for elderly people with hypertension, one of which is non-pharmacological medicine, namely hypertension exercises and foot massage. Hypertension is a cardiovascular disease that can cause complications in the brain, eyes, heart, kidneys, and peripheral blood vessels. Hypertension is a condition where a person experiences an increase in blood pressure above normal which can result in morbidity and mortality. This community service was carried out for 3 days at the Dusun Tamelang Elderly Posyandu which was carried out on 20 respondents of hypertension gymnastics and 20 respondents of foot massage. This community service activity involves students, lecturers and cadres of Dusun Tamelang. The stages of activities discussed were blood pressure checks, as well as demonstrating hypertension exercises and foot massage for elderly people with hypertension. The evaluation results of the implementation of this complementary alternative medicine activity are that most of the community understands and is able to demonstrate hypertension gymnastics and foot massage independently and wants to continue activities at their respective respondents' homes. The result of this community service is a decrease in blood pressure in the elderly with hypertension in Mekarjaya Village. This community service activity can be a hypertension prevention program in lowering blood pressure, one of which is by doing complementary therapy, namely hypertension exercises and foot massage